Computer-assisted Writing: An Investigation of Metacognitive Awareness of Writing Strategies of Iranian EFL Learners - Mokhtarnia, Shabnam; Alavi, Mohammad (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The purpose of this study was to compare the reported use of writing strategies of Iranian EFL learners in two different venues of technology-assisted and conventional writing classes. Overall, thirty two EFL students participated in this study, eighteen in a technology-assisted and fourteen in a conventional English class who responded to a 64-item Likert scale writing strategy inventory adapted from Wei and Chen (2004) and Griffiths and Jordan (2005). The results of the independent sample t-tests revealed that there was a statistically significant difference between the reported use of language-related writing strategies. The results of the paired-sample t-tests, in addition, demonstrated that just in the technology-assisted environment, there was a statistically significant difference for the constructs of language-related and organization strategies and writing experience. The results of this study could carry significant implications for technology-assisted writing instruction in EFL contexts.